Using a decision support system tool for healthcare technology assessments. - Sloane, E.B.
This article discusses a healthcare technology assessment application using a well-developed business tool from the operations research/operations management (OR/OM) field, the analytic hierarchy process (AHP). The AHP methodology provides a proven, structured, and well-documented tool for conducting HTAs for hospitals, integrated delivery networks, or other healthcare providers. A case study based on the selection of a neonatal ventilator is used to illustrate a successful use of the AHP for HTA. Clinical engineers can use this design as a prototype for performing HTAs in their own institutions.
Keywords: Analytic hierarchy process; Clinical engineers; Decision support system; Healthcare providers; Healthcare technology assessments; Hospitals; Integrated delivery networks; Neonatal ventilator; Operations research/operations management field; Well-developed business tool